Categorization of Master-Slave Dialectic in Short Science Fiction Films Generated by Artificial Intelligence That are Broadcasted on YouTube - Rachel Helensky Shambhala; Jandy Edipson Luik; Chory Angela Wijayanti (Institute of Research and Community Outreach - Petra Christian University, 2025)
The rapid evolution of artificial intelligence (AI) has transformed the creative industry, enabling machines to generate images and videos that can be compiled into narrative short films. This technological shift raises important questions about authorship, control, and meaning-making in digital media. This study aims to investigate how the master-slave dialectic, a philosophical concept describing power dynamics between entities, is portrayed in AI generated science fiction short films. Using qualitative content analysis, 10 AI generated short films were examined to identify how messages related to this dialectic are communicated. The analysis reveals three major categories, vulnerability, alienated, and automation. With vulnerability and automation being most prominently depicted, while alienated appears more subtly. Across these categories, eight subcategories were identified, including two new ones which are acceptance and rebellion, that extend Coeckelbergh’s framework and reflect diverse human responses to technological dominance. These results demonstrate that AI generated films can convey complex socio-technical tensions and function as an emerging form of mass communication, contributing to the discourse on human and technology relations in contemporary media.